Restoration of miR-23a expression by chidamide sensitizes CML cells to imatinib treatment with concomitant downregulation of CRYAB. Issue 4 (1st April 2022) - Zhu, Xunxun; Zhang, Jingru; Sun, Yanping; Wang, Yan; Liu, Qian; Li, Peng; Yu, Shuang; Liu, Na; Ye, Jingjing; Ma, Daoxin; Ji, Chunyan
ABSTRACT: MicroRNAs (miRNAs) are involved in various processes from the initiation and development of cancers, including chronic myeloid leukemia (CML). In this report, we aimed to investigate the roles of miR-23a in the regulation of imatinib mesylate (IM) sensitivity in CML cells and the possible mechanisms involved in this process. We demonstrated that the expression of miR-23a was markedly low in bone marrow mononuclear cells from patients in whom IM treatment had failed and imatinib-resistant K562/G01 cells when compared to patients with optimal responses and imatinib-sensitive K562 cells, respectively. Overexpression of miR-23a was shown to induce apoptosis of K562/G01 cells and sensitize these cells to imatinib treatment. With the aid of bioinformatics analysis, we revealed that CRYAB could be a potential downstream effector of miR-23a, contributing to miR-23a-mediated IM resistance. We also observed that the expression of CRYAB was inversely correlated with miR-23a expression in CML cell lines and patient samples. Importantly, chidamide upregulated miR-23a expression and reversed the IM resistance of CML cells. Together, these findings strongly suggest that miR-23a acts as a tumor suppressor by downregulating CRYAB expression. Restoration of miR-23a by chidamide may therefore have a therapeutic effect in controlling the sensitivity of CML cells to imatinib. Graphical abstract: uf0001